THE IMPACT OF LOCAL TIKTOK INFLUENCERS AND USER RESPONSES ON CONTENT VIRALITY TOWARDS PURCHASE DECISION OF F&B MSMEs IN MEGAMAS MANADO - Supeno, Rya Anggreni; Saerang , David P.E; Rogi , Mirah H. (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
In today's digital era, social media has become a dominant marketing tool, with TikTok emerging as one of the fastest-growing platforms. TikTok serves as a key medium for businesses to capture consumer attention through content created by influencers. This study aims to examine the effectiveness of local TikTok influencers and user responses to content virality in shaping consumer purchase decisions for micro, small, and medium enterprises (MSMEs) in the food and beverage (F&B) sector in Megamas Manado. This research employs a quantitative approach using a survey method targeting TikTok users who frequently engage with content from local influencers. Data were analyzed using multiple linear regression to examine the relationships between the study variables. The findings reveal that local TikTok influencers have a significant impact on consumer purchase decisions, both directly and through the virality of the content they produce. Additionally, user responses—such as likes, comments, and shares—contribute to increasing the reach and marketing effectiveness of MSMEs. These findings provide valuable insights for marketers and business owners in leveraging digital strategies to enhance business competitiveness. By understanding the dynamics of social media interactions, MSMEs can optimize the use of local influencers and viral content as effective promotional tools.